Measurement of gene amplifications related to drug resistance in Plasmodium falciparum using droplet digital PCR - Srisutham, S; Suwannasin, K; Sugaram, R; Dondorp, AM; Imwong, M (BioMed Central, 2021)
Background Copy number variations (CNVs) of the Plasmodium falciparum multidrug resistance 1 (pfmdr1), P. falciparum plasmepsin2 (pfplasmepsin2) and P. falciparum GTP cyclohydrolase 1 (pfgch1) genes are associated with anti-malarial drug resistance in P. falciparum malaria. Droplet digital PCR (ddPCR) assays have been developed for accurate assessment of CNVs in several human genes. The aim of the present study was to develop and validate ddPCR assays for detection of the CNVs of P. falciparum genes associated with resistance to anti-malarial drugs. Methods A multiplex ddPCR assay was developed to detect the CNVs in the pfmdr1 and pfplasmepsin2 genes, while a duplex ddPCR assay was developed to detect CNV in the pfgch1 gene. The gene copy number (GCN) quantification limit, as well as the accuracy and precision of the ddPCR assays were determined and compared to conventional quantitative PCR (qPCR). In order to reduce the cost of testing, a multiplex ddPCR assay of two target genes, pfmdr1 and pfplasmepsin2, was validated. In addition, the CNVs of genes of field samples collected from Thailand from 2015 to 2019 (n = 84) were assessed by ddPCR and results were compared to qPCR as the reference assay. Results There were no significant differences between the GCN results obtained from uniplex and multiplex ddPCR assays for detection of CNVs in the pfmdr1 and pfplasmepsin2 genes (p = 0.363 and 0.330, respectively). Based on the obtained gene copy number quantification limit, the accuracy and percent relative standard deviation (%RSD) value of the multiplex ddPCR assay were 95% and 5%, respectively, for detection of the CNV of the pfmdr1 gene, and 91% and 5% for detection of the CNV of the pfplasmepsin2 gene. There was no significant difference in gene copy numbers assessed by uniplex or duplex ddPCR assays regarding CNV in the pfgch1 gene (p = 0.276). The accuracy and %RSD value of the duplex ddPCR assay were 95% and 4%, respectively, regarding pfgch1 GCN. In the P. falciparum field samples, pfmdr1 and pfplasmepsin2 GCNs were amplified in 15% and 27% of samples from Ubon Ratchathani, Thailand, while pfgch1 GCN was amplified in 50% of samples from Yala, Thailand. There was 100% agreement between the GCN results obtained from the ddPCR and qPCR assays (κ = 1.00). The results suggested that multiplex ddPCR assay is the optional assay for the accurate detection of gene copy number without requiring calibration standards, while the cost and required time are reduced. Based on the results of this study, criteria for GCN detection by ddPCR analysis were generated. Conclusions The developed ddPCR assays are simple, accurate, precise and cost-effective tools for detection of the CNVs in the pfmdr1, pfplasmepsin2 and pfgch1 genes of P. falciparum. The ddPCR assay is a useful additional tool for the surveillance of anti-malarial drug resistance.